Relative pedaling forces are low during cycling - Barranco-Gil, D.; Hernández-Belmonte, A.; Iriberri, J.; Martínez-Cava, A.; Buendía-Romero, Á.; Alejo, L. B.; Rodríguez-Rielves, V.; Sanchez-Redondo, I. R.; de Pablos, R.; Lucia, A.; Valenzuela, P. L.; Pallares, J. G. (Journal of Science and Medicine in Sport, 2024)
We quantified and compared the mechanical force demands relative to the maximum dynamic force (MDF) of 11 cyclists when pedaling at different intensities (ventilatory threshold, maximum lactate steady state, respiratory compensation point, and maximal aerobic power), cadences (free, 40, 60 and 80rpm), and all-out resisted sprints. Relative force demands (expressed as %MDF) progressively increased with higher intensities (p<0.001) and lower cadences (p<0.001). Notwithstanding, relative force demands were low (< 54% MDF) for all conditions, even during the so-called `torque training`. These results might be useful when programming on-bike resistance training to improve torque production capacity.